2017
DOI: 10.1371/journal.pone.0184138
|View full text |Cite
|
Sign up to set email alerts
|

Unmet healthcare needs in homeless women with children in the Greater Paris area in France

Abstract: BackgroundDespite their poor health status, homeless women encounter many barriers to care. The objectives of our study were to estimate the prevalence of unmet healthcare needs in homeless women and to analyse associated relationships with the following factors: financial and spatial access to care, housing history, migration status, healthcare utilisation, victimization history, caring for children, social network and self-perceived health status.MethodsWe used data from 656 homeless women interviewed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
(71 reference statements)
1
40
0
1
Order By: Relevance
“…Unmet healthcare needs were reported in 13 studies (Baggett et al, ; Biederman et al, ; Corrigan et al, ; Hwang et al, ; Kertesz et al, ; van Laere et al, ; Martins, ; Nickasch & Marnocha, ; Rae & Rees, ; Robbins et al, ; Uddin et al, ; Vuillermoz et al, ; Zur & Jones, ). Highest prevalence of unmet need in the past 6 months (82%) was reported in a study of injection drug users in the United States (Robbins et al, ), whereas the lowest prevalence of unmet healthcare needs (17%) was reported in a study from Canada (with universal healthcare), investigating a mixed population of persons experiencing homelessness (Hwang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Unmet healthcare needs were reported in 13 studies (Baggett et al, ; Biederman et al, ; Corrigan et al, ; Hwang et al, ; Kertesz et al, ; van Laere et al, ; Martins, ; Nickasch & Marnocha, ; Rae & Rees, ; Robbins et al, ; Uddin et al, ; Vuillermoz et al, ; Zur & Jones, ). Highest prevalence of unmet need in the past 6 months (82%) was reported in a study of injection drug users in the United States (Robbins et al, ), whereas the lowest prevalence of unmet healthcare needs (17%) was reported in a study from Canada (with universal healthcare), investigating a mixed population of persons experiencing homelessness (Hwang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies relevant to our aim and research questions were included in the review, 11 quantitative (Asmoredjo, Beijersbergen, & Wolf, ; Baggett, O'Connell, Singer, & Rigotti, ; Hwang et al, ; Jenkins & Parylo, ; Kertesz et al, ; van Laere, de Wit, & Klazinga, ; Robbins, Wenger, Lorvick, Shiboski, & Kral, ; Uddin et al, ; Vuillermoz, Vandentorren, Brondeel, & Chauvin, ; Whelan et al, ; Zur & Jones, ), and 11 qualitative (Biederman, Gamble, Manson, & Taylor, ; Biederman, Nichols, & Lindsey, ; Bungay, ; Corrigan, Pickett, Kraus, Burks, & Schmidt, ; Gültekin, Brush, Baiardi, Kirk, & VanMaldeghem, ; Kryda & Compton, ; Martins, ; McLeod & Walsh, ; Nickasch & Marnocha, ; Rae & Rees, ; Voronka et al, ). We found no studies that described economic costs in conjunction with needs of health‐ and social care in persons experiencing homelessness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations